Distinct dimensions of depression are associated with different brain‐related biomarkers. (20th December 2022) - Soleimani, Laili; Beeri, Michal Schnaider; Heymann, Anthony; Livny, Abigail; Lesman‐Segev, Orit H.; Lin, HungMo; Ouyang, Yuxia; Ravona‐Springer, Ramit
Abstract: Background: Management of depression, a potentially modifiable risk factor for dementia, is of great importance in older adults with Type 2 Diabetes (T2D), specifically because of their higher risk for both conditions. We previously showed in older adults (aged ≥65) with T2D in the Israel Diabetes and Cognitive Decline (IDCD) study, that different depression‐dimensions were associated with distinct patterns of cognitive outcomes. Specifically, apathy, but not other depression‐dimensions, was associated with faster decline in executive functions. Here, we investigated the cross‐sectional relationship between depression‐ dimensions with different neuropathologies, i.e., total gray matter (GM) volume, white matter hyper‐intensities (WMH) and amyloid burden. Method: Among IDCD participants [mean age = 70.55 (SD = 4.25), 38.5% female], 209 had a brain MRI, 42 of whom also had an amyloid PET. Depression dimensions were defined based on the Geriatric Depression Scale‐ 15 item (GDS‐ 15): dysphoric mood, apathy, anxiety, hopelessness and subjective memory complaint. Gray Matter and WMH volumes were examined using a high‐resolution 3‐Tesla brain MRI. Amyloid‐β burden was defined as mean standardized uptake value ratios (SUVRs) of [18F] flutemetamol in the frontal, parietal, and temporal cortices compared to the cerebellum as reference region. We used two‐step linear regression models to study the association of GDS–domains and brain imaging markers. Result: Higher total GDS score was associated with lower GM volume (r = ‐0.14; p = 0.037) and higher volume of WMH (r = 0.20; p = 0.003), but not with brain amyloid‐β burden (r = ‐0.13; p = 0.37). Among specific depression‐ dimensions, apathy (r = 0.22; p = 0.001), and hopelessness (r = 0.15; p = 0.033) were associated with higher WMH burden, whereas the subjective memory complaints dimension was associated with lower total GM volume (r = ‐0.15; p = 0.026). Depression dimensions were not associated with amyloid burden. Conclusion: In cognitively normal older adults with T2D, higher depression scores, even below the cutoff defined as clinically significant, were associated with lower GM and higher WMH volumes. Apathy was the main driver of the association with higher WMH burden and subjective memory complaints drove the association with brain atrophy. No association was found between depression‐dimensions and amyloid‐β burden, consistent with previous findings in non‐T2D samples, on the role of vascular, rather than AD pathology, in depression.